Social aspects in the economic behavior of information users - N.Ya. Marchyshyn (Економіка, управління та адміністрування)
In the modern information society, the study of social aspects in the economic behavior of information users is becoming more and more relevant. With the deepening of the use of social networks, the development of a global community and the increase of access to information, the importance of understanding social factors in economic processes becomes an extremely important issue that cannot be ignored. Decisions made at the level of individuals, groups, business entities or society as a whole have a decisive influence on the formation of not only consumer behavior and habits, but also on economic trends and business development. Disclosure of social aspects is an important component for understanding modern economic realities and forecasting future directions of development. As a result of the research, the key factors that determine people's decisions in the economic sphere and their influence on the processes of management decision-making in business were identified and analyzed. These findings help to better understand possible changes in the economic environment and their possible consequences for society as a whole. The research results open up new opportunities for analyzing and forecasting economic trends, and also provide valuable information for developing management strategies and making effective economic decisions.